Gyrokinetic simulation of low-frequency Alfvénic modes in DIII-D tokamak. (23rd April 2021) - Choi, G.J.; Liu, P.; Wei, X.S.; Nicolau, J.H.; Dong, G.; Zhang, W.L.; Lin, Z.; Heidbrink, W.W.; Hahm, T.S.
Abstract: Global gyrokinetic simulations find that a beta-induced Alfvén eigenmode (BAE) and a low-frequency mode (LFM) co-exist in the DIII-D tokamak experiments. The simulated LFM mode structure and many of its parametric dependencies are consistent with experimental observations. The LFM can be excited without fast ions and has a frequency inside the gap of the beta-induced Alfvén-acoustic eigenmode (BAAE). However, an antenna scan shows that it is NOT the conventional BAAE. Instead, the LFM is an interchange-like electromagnetic mode excited by non-resonant drive of pressure gradients. Furthermore, the simulated BAE mode structure is consistent with the experiment but the frequency is lower than the experiment. The compressible magnetic perturbations significantly increase the growth rates of the BAE and LFM. On the other hand, trapped electrons and equilibrium current have modest effects on the BAE and LFM.